Particularities of consumer`s behavior in the context of COVID 19 pandemic - Veselova, Andzela (University of Latvia, 2021)
Marketing activities often influence the given circumstances in the given settings in order to emphasize or gradually create the predictable consumers’ behaviour. It works very well, if the context of available opportunities, overall structure and logic are principally stable and unchanging. Coronavirus has blown up everyone’s mind, destabilizing the settings all over the world. If the disease spreads over, the rate of instability subject to constant changes increases and world functions without a predictable context or models. A human being adapts to changing, unstable environment and takes different decisions. The sales increased and the flow of new customers rocketed literally. Online shopping probably was a part of daily life of the people of the new millennium; however, COVID -19 pandemic has also encouraged the older generation to buy the tickets online, and many of them did this for the first time in their lives. E-commerce offers to the consumers not only the comfort, but also the opportunity to find the best offers, which is particularly valuable in today’s insecure financial situation. At the same time, despite certain precaution measures, many consumers show openness and curiosity. The aim of the research is to study the behaviour of the consumers and basing on theoretical concepts and ideas to study the particularities of consumers’ behaviour in the context of COVID -19 impact as well as draw conclusions and give recommendations. The tasks are: 1) explore theoretical aspects based on consumer behaviour in the COVID -19 context; 2) describe secondary data from statistical report of consumer behaviour of COVID -19 context; 3) draw conclusions and recommendations. The methodology of the research will include a monographic method, analysis of statistical data, deductive and graphic method.
Keywords: behaviour; consumer; COVID-19; products; Research Subject Categories::SOCIAL SCIENCES